Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Pembelajaran Biologi Berbasis STEM Pada Materi Sistem Pernapasan Manusia Di Kelas XI MIA SMA Swasta Deli Murni Bandar Baru Tahun Pembelajaran 2020/2021 - Eci Elviani Samosir; Mariaty Sipayung (Program Studi Pendidikan Biologi, 2022)
ABSTRACT This study aims to design and produce Student Worksheets (LKPD) based on the Science Engineering Technology and Mathematics Approach (STEM) on the subject of Human Respiratory System. The research design used is a type of research and development. Subjects in this study were Material Experts, Learning Experts, Design Experts, Biology Study Teachers and XI-MIA-A Class Deli Murni Private High School Bandar Baru. Data collection was carried out with instruments in the form of respons sheets. Data analysis used quantitative and qualitative descriptive analysis. The design of the LKPD based onthe STEM Approach was carried out using the 4-D instructional development model, namely through the stages of Define, Design, Development, and Dessiminate. The results showed that the design of the LKPD based on the STEM Approach based on the assessment of material experts obtained an average percentage of 87,5% with very appropriate criteria, the assessment of learning experts obtained an average percentage of 92,5% with very appropriate criteria, the design expert's assessment obtained an average percentage of 78,7% of the eligible criteria for the evaluation of Biology Study Teachers obtained an average percentage of 87,96% with a very feasible rating category and classical learning completeness obtained an percentage of 91%, while the results of responses / responses from students obtained an average percentage of 93,0% with good assessment criteria.The results of the use of the LKPD Based on the STEM Approach designed obtained an average score of 82.96 with a total of 27 students completed. STEM-based LKPD on the material for Human Respiratory System that has been designed obtains